2020
DOI: 10.1038/s41598-020-62230-5
|View full text |Cite
|
Sign up to set email alerts
|

Haemorrhagic transformation following ischaemic stroke: A retrospective study

Abstract: The aim of this study was to identify the prevalence of haemorrhagic transformation (HT) in patients with ischaemic stroke, and evaluate its association with medical comorbidities, stroke subtypes, premorbid medication, and long-term survival. To achieve this, we performed a retrospective analysis of 527 consecutive stroke rehabilitation patients. Of these, 102 (19.4%) developed HT. Older patients, and those with large artery strokes, had a higher risk of HT. Forty-one patients received alteplase (rtPA), of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 33 publications
(43 reference statements)
2
28
1
Order By: Relevance
“…This is supported by the fact that a BBB disruption measured in the first hours of stroke does not predict the appearance of HT occurring later than 3 days ( 129 ). It is thought that late HT occurs due to increased BBB permeability and blood flow after cerebral edema reduction ( 130 , 131 ). The hemorrhage appearance differs according to the stage it occurs.…”
Section: Hemorrhagic Transformation: the Role Of Bbb Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by the fact that a BBB disruption measured in the first hours of stroke does not predict the appearance of HT occurring later than 3 days ( 129 ). It is thought that late HT occurs due to increased BBB permeability and blood flow after cerebral edema reduction ( 130 , 131 ). The hemorrhage appearance differs according to the stage it occurs.…”
Section: Hemorrhagic Transformation: the Role Of Bbb Permeabilitymentioning
confidence: 99%
“…Of the patients presenting with HT in the acute phase, 25% have had received reperfusion therapy, while only 16.7% of the late HT patients did ( 131 ). In another cohort of 527 patients, 86.3% of patients with HT developed it in the first 48 h ( 130 ). Montaner et al showed that 68.75% of patients with HT presented it in the first 48 h. Interestingly, seven of the 11 patients developing HT in the first 48 h had recanalization in the first 12 h, while none of the patients with HT beyond 48 h had early recanalization ( 110 ).…”
Section: Hemorrhagic Transformation: the Role Of Bbb Permeabilitymentioning
confidence: 99%
“…Despite HT is a serious complication commonly following reperfusion therapy and, sometimes as a result of the natural evolution of the disease [13], the current treatment recommendations include anticoagulants, thrombolysis, and intravascular procedures [14]. Thus, available and routine clinical prediction tools of HT based on pathophysiological mechanisms are necessary to decide the best management options according to the patient's system response to stroke.…”
Section: Discussionmentioning
confidence: 99%
“…HT is divided into hemorrhagic infarction (HI) and parenchymal hematoma (PH) types [ 2 ]. Patients with HI-type HT have no significantly higher risk of neurological deterioration than patients without HT, but patients with PH-type HT have symptomatic clinical deterioration [ 1 , 2 , 3 , 4 ]. According to a previous study, only PH-type HT in ischemic stroke is associated with early or late symptomatic neurological deterioration; we therefore wanted to focus on the risk factors associated with the occurrence of PH-type HT [ 4 ].…”
Section: Introductionmentioning
confidence: 99%